IoT Based Personal Safety And Protection System - Liau, Kai Hao (2021)
As urbanisation becomes more rapid, the problem of poverty has become more serious, and the poor can only try to harm others to get money for living. To guarantee the safety of an individual, the Internet of Things (IoT) based personal security or protection systems are introduced. However, the conventional systems do not offer a constant performance, in which their triggering methods are too simple and impractical in the real world. They have no measure on false alarm prevention, causing unstable performance of the systems. In this project, IoT technology is applied to develop a more reliable personal safety and protection system that can automatically respond against dangerous situations with three activation methods that avoid false alarms and store the data in the Firebase database. There are four major parts in the proposed system, which are sensing, processing, actuating, and visualising units. The sensing unit is an integration of sensors and receivers that receives input continuously, while the actuating unit is a combination of actuators that carry out response towards an emergency. Besides, the processing unit is a Raspberry Pi, while the visualising unit is an Android application that communicates with the Firebase database. Real-time monitoring and controlling of the system are achieved by the communication between the Firebase real-time database and Android application. Experiments are conducted on the proposed system, and the results have proved its functionality, accuracy, and precision.